Multiaxial elastoplastic cyclic loading of austenitic 316L steel - V. Mazánová; J. Polák; V. Škorík; T. Kruml (Fracture and Structural Integrity)
Cyclic stress-strain response and fatigue damage character has been investigated in austenitic stainless steel 316L. Hollow cylindrical specimens have been cyclically deformed in combined tension-compression and torsion under constant strain rate condition and different constant strain and shear strain amplitudes. In-phase and 90° out-of-phase cyclic straining was applied and the stress response has been monitored. Cyclic hardening/softening curves were assessed in both channels. Cyclic softening followed for higher strain amplitudes by long-term cyclic hardening was observed. Cyclic stress-strain curves were determined. Study of the surface damage in fractured specimens revealed the types and directions of principal cracks and the sources of fatigue crack initiation in slip bands.